An Asian Ground Beetle, Mochtherus tetraspilotus (MacLeay) (Coleoptera: Carabidae: Lebiini) - Paul M. Choate (EDIS)
Mochtherus tetraspilotus (MacLeay) was first detected in southern Florida in 1992. Since then specimens have been collected in Gainesville and at Archbold Biological Station in Highlands County. Adult members of this group of Carabidae are known to be predators. The impact of this species on our native species remains to be determined, as does the source of introduction. Its rapid spread in Florida suggests that it may soon be found throughout the Gulf States. This 2-page fact sheet was written by Paul M. Choate and published by the UF Department of Entomology and Nematology, September 2012.